Properties of fly ash cement brick containing palm oil clinker as fine aggregate replacement - Khairunisa, Muthusamy; Budiea, Ahmed Mokhtar Albshir; Sharifah Maszura, Syed Mohsin; Nur Sahira, Muhammad Zam; Nor Ezzaty, Ahmad Nadzri (Elsevier Ltd, 2020)
Environmental pollution caused by disposal of by-product from local industries namely fly ash from coal power plant and palm oil clinker generated by palm oil mills needs to be resolved. This research examines the effect of palm oil clinker as partial sand replacement on properties of fly ash cement sand brick. Five brick mixes were prepared using fly ash blended cement as the binder. Other mixes were produced by varying the quantity of pulverised palm oil clinker ranging from 0%, 10%, 20%, 30% and 40% by weight of sand. All specimens were water cured for 28 days. The specimens were subjected to compressive strength, flexural strength and water absorption test. Utilization optimum amount of clinker of 30% enhances the brick strength owing to the pozzolanic effect of fine clinker. The chemical reaction between calcium hydroxide and silicon dioxide forms extra CSH gel that contributes to pore refinement and higher strength of brick.